(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
In this paper the FE simulation and experimental equipment and design of the system for deformation by single point incremental sheet metal forming are presented. The formability is executed at room temperature and needs the milling machine, the tool of hemispherical head and toroidal head applied to deform the sheet, whereas translates from the peripheral of the sheet to its focus that additionally driving the sheet down. The blank is distorted increment by increment into the required shape via hemispherical or toroidal nose instrument going along a circular way. In the present investigation, the deformation’s analyses were down on the aluminum 7075 compound with thickness (0.9mm) and various device nose are enormously impact on the contact region and its observed that the hemispherical apparatus gives the best outcome. Close to this investigation consequence of the impact of shaping instrument nose on the formability is displayed. The ANSYS results are comparison with results obtained experimentally and it's discovered the deviation about 8% and this is expected to the criteria of spring-back.